Islamic Instructional Leadership and Its Influence on Teaching Quality at Pondok Pesantren Wali Songo Sragen - Purwati, Dwi; Putri, Rizki Alifia; Sutama, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to examine the implementation of Islamic instructional leadership and its influence on the quality of teaching at Pondok Pesantren Wali Songo Sragen, a pesantren that integrates traditional Islamic values with a formal education system. In response to the demands for educational improvement and innovation, there is a need for a leadership model that is not only instructionally effective but also aligned with religious values. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that leadership at this pesantren emphasizes role modeling (uswah), trust-based mentoring, and moralspiritual guidance in efforts to improve teacher performance. Teachers demonstrated significant improvements in lesson planning, implementation, and evaluation, driven by leadership grounded in Islamic values such as amanah (trustworthiness), ikhlas (sincerity), and syura (consultation). This research contributes theoretically by offering a contextual adaptation of the instructional leadership model in Islamic education. Practically, the findings provide a framework for pesantrens and Islamic schools seeking to enhance learning quality through valuebased leadership. The study also underscores the importance of institutional support to sustain Islamic leadership beyond reliance on individual charisma.